2007
DOI: 10.1007/s00540-007-0520-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sevoflurane and/or nitrous oxide on bacterial growth in in vitro culture conditions

Abstract: The aim of this study was to determine the role of sevoflurane and/or nitrous oxide on bacterial growth under conditions in vitro similar to those of clinical practice. We assessed these effects on Pseudomonas aeruginosa, Acinetobacter lwoffii, and Staphylococcus aureus growth. Bacterial inoculums were prepared from reference strains in nutritive broth. Airtight chambers were filled with bacterial suspensions. Each strain was studied with and without exposure to sevoflurane and/or nitrous oxide at baseline, af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…27 Interestingly, in a cell-culture study, nitrous oxide also accelerated the growth of microorganisms. 28 This study, together with previous laboratory findings, 26,27 highlights the worst case scenario where host defense is impaired in the presence of bacterial overgrowth. In humans, several studies have reported an increase in DNA damage among operating room personnel who are regularly exposed to nitrous oxide compared with those healthcare workers working in other areas of the hospital.…”
Section: Discussionsupporting
confidence: 61%
“…27 Interestingly, in a cell-culture study, nitrous oxide also accelerated the growth of microorganisms. 28 This study, together with previous laboratory findings, 26,27 highlights the worst case scenario where host defense is impaired in the presence of bacterial overgrowth. In humans, several studies have reported an increase in DNA damage among operating room personnel who are regularly exposed to nitrous oxide compared with those healthcare workers working in other areas of the hospital.…”
Section: Discussionsupporting
confidence: 61%
“…Previous research solely studied the effect of anesthetics on bacterial growth, as the association between the severity of bacterial infection and higher bacterial load is intuitively clear, and has been supported by the literature [35]. Most of the previous studies suggest that volatile anesthetics at clinically relevant concentrations do not affect bacterial growth as summarized in Table 1 [610]. In contrast, the effect of anesthetics on other bacterial behaviors including motility and biofilm formation has seldom been studied.…”
Section: Introductionmentioning
confidence: 93%
“…9 Karabiyik et al assessed the antibacterial effects of sevoflurane and nitrous oxide and concluded that the antibacterial effects of inhalation anaesthetics depend on the duration of anesthesia and type of micro-organism. 10 In our case, the infection symptoms such as, local signs and systemic fever were missing and only laboratory findings showed positive wound culture. Nevertheless, P.aeruginosa growth in wound culture turned into negative after topical sevoflurane treatment without any systemic antibiotic treatment.…”
Section: Discussionmentioning
confidence: 58%